Business modeling and software design : 7th International Symposium, BMSD 2017, Barcelona, Spain, July 3-5, 2017, revised selected papers /: 7th International Symposium, BMSD 2017, Barcelona, Spain, July 3-5, 2017, revised selected papers. (2018) - Unknown
No abstract available